Regional technological capabilities and green opportunities in Europe - Nicolò Barbieri; Davide Consoli; Lorenzo Napolitano; François Perruchas; Emanuele Pugliese; Angelica Sbardella (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
The goal of the paper is to elaborate an empirical overview of green technological development in European regions. This is a timely pursuit considering the ambitious commitments stipulated in the recent European Green Deal to achieve climate neutrality by 2050. Our analysis is organised in three steps. First, we map the geographical distribution of innovative activities in Europe and profile regions in terms of technological capabilities. Second, we elaborate a metric to identify regions' green innovation potential. Third, we check whether possessing comparative advantage in specific technological domains is associated with a region's capacity to develop green technologies.
Keywords: O32; Q01; Q55; 330; Green Technology; European regions; Economic Fitness and Complexity